2019
DOI: 10.1590/1983-40632019v4958011
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of leguminous species as cover crops associated with sacha inchi1

Abstract: Sacha inchi (Plukenetia volubilis) is an oilseed crop that has gained importance due to the high contents of proteins and unsaturated fatty acids in its seeds. This study aimed at evaluating the growth characteristics of five leguminous species (Crotalaria juncea,Centrosema macrocarpum,Arachis pintoi,Cannavalia ensiformis and Phaseolus vulgaris) used as cover crops, as well as determining their influence on the sacha inchi yield. A complete randomized block design, with three blocks, was used. C. macrocarpum a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Conversely, rice plants can thrive and reach their maximum yield potential when weed growth is limited, inhibited or absent. Practically, A. pintoi has been reported as a promising green manure with multiple benefits comprising soil coverage and nitrogen fixation [20,21,24,25]. In addition, other studies have demonstrated that the growth and yield components of corn (Zea mays) and tomato (Solanum lycopersicum) were significantly enhanced using a living mulch of A. pintoi [51][52][53] that concurrently reduced weed growth in some tropical upland crops as well as improving soil fertility and erosion [53].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, rice plants can thrive and reach their maximum yield potential when weed growth is limited, inhibited or absent. Practically, A. pintoi has been reported as a promising green manure with multiple benefits comprising soil coverage and nitrogen fixation [20,21,24,25]. In addition, other studies have demonstrated that the growth and yield components of corn (Zea mays) and tomato (Solanum lycopersicum) were significantly enhanced using a living mulch of A. pintoi [51][52][53] that concurrently reduced weed growth in some tropical upland crops as well as improving soil fertility and erosion [53].…”
Section: Discussionmentioning
confidence: 99%
“…Although extensive studies on the cover crop of A. pintoi have been carried out [20,21,24,25], little work has been conducted on evaluating the allelopathic potential of this legume. Therefore, the aims of this study were (i) to assess the allelopathic activity of A. pintoi aerial parts of powder against the germination and growth of E. crus-galli and various tested plants, especially on paddy weeds through bioassays and greenhouse and field trials; (ii) to determine total phenolic and flavonoid contents and inhibitory effects from the different solvent extracts (methanol, hexane and ethyl acetate); (iii) to analyze its potential allelochemicals using gas chromatography-mass spectrometry (GC-MS).…”
Section: Introductionmentioning
confidence: 99%
“…Alegre et al (2017) reported that degraded lands with low fertility, affected by overgrazing in the humid tropics of Yurimaguas, can be recovered for sustainable production with leguminous cover crops and Multistrata Agroforestry Systems (MAS) because in a short time soil, compaction is reduced and organic matter level increased after the establishment of cover crops and trees. Furthermore, the use of leguminous cover crops influences in the increase of tropical crops yield (Solis et al, 2019).…”
Section: General Sustainabilitymentioning
confidence: 99%